The Impact of Tourism on Changes in Social Values Within Communities - Fahriza Izzana; Sri Widayati; M. Lutfi Baehaqi (Borong Newinera Publisher, 2026)
This study aims to analyze the impact of tourism on social values in Alang-alang Hamlet, RT 03 RW 04, Karimunjawa Village, Karimunjawa Subdistrict, Jepara Regency. Karimunjawa is a marine tourism destination that is well known among local and foreign communities. This study uses a qualitative descriptive method with triangulation data collection techniques, namely through observation, interviews, and documentation studies. Data analysis was carried out according to Miles and Huberman's theory in order to obtain accurate information to maintain data validity. The results show that tourism has a significant impact on social values, including the values of mutual cooperation, social solidarity, and social tolerance. Based on the results of the study, it can be concluded that the impact of tourism on changes in social values does not necessarily have a negative influence, but can create new forms of social activities that are positive in value to face the challenges of modern tourism.